NEW TECHNOLOGIES FOR OBTAINING DRY CONSTRUCTION MIXTURES BASED ON DOMESTIC INDUSTRIAL WASTE - H. S. Solijonov (Web of Journals Publishing, 2025)
This article covers the results of research on obtaining binders for dry building mixtures based on asbestos-cement waste, increasing the hydraulic activity of asbestos-cement waste (ACW), the effect of filler on the physical-mechanical properties of asbestos–cement waste-based binder, the effect of plasticizing additives on the rheological and physical-mechanical properties of dry building mixtures based on asbestos-cement waste, and physical chemical analysis of.
Keywords: Physical chemical analysis of industrial waste, asbestos cement waste (ACW), microsilica, dry construction mixtures with new composition, physical and mechanical properties, rheological and physical and mechanical properties, plasticizing additives, dry construction mixture compositions based on asbestos–cement waste.